The Influence of Plant Isoflavones Daidzein and Equol on Female Reproductive Processes - Alexander V. Sirotkin; Saleh Hamad Alwasel; Abdel Halim Harrath (Pharmaceuticals, 2021)
In this review, we explore the current literature on the influence of the plant isoflavone daidzein and its metabolite equol on animal and human physiological processes, with an emphasis on female reproduction including ovarian functions (the ovarian cycle; follicullo- and oogenesis), fundamental ovarian-cell functions (viability, proliferation, and apoptosis), the pituitary and ovarian endocrine regulators of these functions, and the possible intracellular mechanisms of daidzein action. Furthermore, we discuss the applicability of daidzein for the control of animal and human female reproductive processes, and how to make this application more efficient. The existing literature demonstrates the influence of daidzein and its metabolite equol on various nonreproductive and reproductive processes and their disorders. Daidzein and equol can both up- and downregulate the ovarian reception of gonadotropins, healthy and cancerous ovarian-cell proliferation, apoptosis, viability, ovarian growth, follicullo- and oogenesis, and follicular atresia. These effects could be mediated by daidzein and equol on hormone production and reception, reactive oxygen species, and intracellular regulators of proliferation and apoptosis. Both the stimulatory and the inhibitory effects of daidzein and equol could be useful for reproductive stimulation, the prevention and mitigation of cancer development, and the adverse effects of environmental stressors in reproductive biology and medicine.